Infeksi Oportunistik Hepatitis B dan Hepatitis C Pada Pasien Terinfeksi Human immunodeficiency Virus yang Menjalankan Terapi Antiretroviral - Doni, Doni Setiawan; Handrianto, Indri; Nur Hidayatuloh, Arif; Nurmalasari, Ary; Farihatun, Atun (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Human immunodeficiency virus is a virus that attacks lymphocytes which can reduce the human immune system, making it more susceptible to various opportunistic infectious diseases and can cause death. This can cause other diseases to infect the body, one of which causes cell inflammation and liver cell necrosis, known as Hepatitis B and Hepatitis C. The aim of this study is to determine the results of Hepatitis B Surface Antigen and Anti-Hepatitis C Virus examinations in patients positive for Human Immunodeficiency Virus. who underwent antiretroviral therapy at one of the Community Health Centers in Ciamis Regency. This research method is descriptive where the research was carried out on Human Immunodeficiency Virus positive patients at one of the Community Health Centers in Ciamis Regency with 35 respondents and the examination was carried out in the Community Health Center laboratory in May 2023. The results of this research obtained 2 (6%) HBsAg positive respondents and 1 (3%) respondent was positive for anti-HCV. In conclusion, HIV patients on antiretroviral therapy are at risk of developing Hepatitis B and Hepatitis C infections.  Key words          : anti-HCV, HBsAg, ELISA, Immunochromatography